Development of Digital-Based Islamic Religious Education Coursebook at Khairun University - Umar, Sitirahia Hi.; Muharram, H.; Niswaty, Risna; Bundu, Patta; Arismunandar; Rasyid, Rusman (International Journal of Integrative Sciences, 2024)
This study aims to develop a valid, practical, and effective digital interactive Islamic education coursebook at Universitas Khairun using the ADDIE development model. The research process began with a needs analysis which indicated that students required a coursebook with simplified content divided into seven main topics. The design phase involved determining the topics, collecting references, creating a matrix, and organizing learning objectives. The developed coursebook underwent two validation steps: expert evaluation and product testing. Expert validation results showed an average score of 3.37, while product testing revealed an increase in pre-test scores from 70.00 to 81.04, a difference of 16.23%. Practicality assessment of the coursebook revealed that 95.07% of respondents rated it as “practical”. Additionally, the effectiveness of the coursebook was demonstrated by a 16.44% increase in the average pre-test and post-test scores of students. These findings indicate that the developed digital Islamic education coursebook meets the criteria for validity, practicality, and effectiveness, making it an effective learning resource at Khairun University